Implementasi Bahan Ajar Berbasis Kain Rentang dan Papan Nama Materi Membaca Cepat di Sekolah Dasar - Muhammad Iqbal Arrosyad; Asyraf Suryadin (Jurnal Inovasi Pendidikan Dasar, 2020)
The purpose of this study is to describe the implementation of banner teaching material and speed reading material nameplate in Elementary Schools and describe the constraints experienced in the implementation of learning using range-based teaching material and speed reading material nameplate in elementary schools. This study used a descriptive qualitative method with data triangulation data collection techniques including participatory observation, in-depth interviews, and documentation. The subjects of this study were students and teachers in class V SD Negeri 24 Pangkalpinang, Bangka Belitung Islands. The results of this study indicate the implementation of teaching materials carried out in four stages namely the action planning stage by preparing a learning implementation plan according to the time and implementation material, the implementation phase of the action by learning Indonesian subjects speed reading material using banner teaching materials and name plate, the results phase observation by observation during the implementation from the beginning to the end of learning, and the reflection stage by assessing how the implementation of learning is carried out from the side of the teacher and students. And the obstacles that were found to be less optimal was because students lacked focus on teaching materials, lack of assistive media such as LCD / Infocus to make students focus and add attention to learning.